Lithium slag leach solution refining by hydroxide precipitation - Klimko J.; Takacova Z.; Marcinov V.; Piroskova J.; Vindt T.; Liptai P.; Orac D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Lithium-ion batteries contain many of critically important metals and their effective recycling is key to the EU’s sustainable development. In the past, only metals such as Co, Ni, and Cu were recycled by pyrometallurgy, while Li and Al were concentrated in the slags and not further processed. The novel approach of pyrometallurgical treatment of the black mass offers the possibility of further hydrometallurgical utilization of the slags. This paper examines the refining of the solution obtained by leaching the slag in sulfuric acid. The most valuable element in the leach solution is Li, but it also contains Al, Si, Co, Mn, Ni and Cu, which must be removed before high-purity Li recovery is possible. Purification is achieved by adjusting the pH by adding NaOH. The results confirm that Al and Mn can be removed by 100%, Si by 93.56%, Cu by 86.36% and Cu by 61.75%. The results also confirmed that solution refining by the adding NaOH causes lithium losses ranging from 10% at pH 7 to 28% at pH 12. Therefore, it is suggested that further solution refining methods should be combined before precipitating pure Li2CO3 with minimal losses.